Eventos adversos de la CPRE en el Hospital de San José de Bogotá (2009)
Endoscopic retrograde cholangiopancreatography (ERCP) has become the preferred treatment method for hepatobiliary and pancreatic disease. Despite technological progress this technique continues to account for the greatest morbidity and mortality caused by digestive endoscopic procedures. ERCP carries a risk of pancreatitis, perforation, hemorrhage, cholangitis and cardiopulmonary events occurring in upto 10% of patients in referral centers, implying a mortality of up to 1%, not including therapeutic failures or the need for re-intervention. A greater mortality rate has been demonstrated in prospective studies rather than in retrospective studies, but overall, the number of complications described in the literature is much lower than the number of complications that actually occur. A descriptive prospective study was conducted at San José Hospital from April 1, 2006 to April 30, 2007 in patients who underwent an ERCP and had a 1-month follow-up. A total of 381 patients were included; 9 (2.3%) were excluded, and of the remaining 372 there was an overall success in 79.6% of cases, 8.3% had a second intervention, 7.6% developed complications (pancreatitis, perforation, hemorrhage, cholangitis, pain, intolerance to sedatives, and cardiopulmonary events), and 4.3% were failed ERCP studies. The mortality rate of the ERCP procedure was 0.8%. ERCP-related complications were determined at a teaching center, and this suggests the need to implement centers of excellence in order to improve the efficacy of the procedure.